2000
DOI: 10.1097/00006123-200005000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Failure of Endoscopic Third Ventriculostomy for Obstructive Hydrocephalus

Abstract: The risk of failure increases with intracerebral infection, likely because of obliteration of cerebrospinal fluid pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
152
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(155 citation statements)
references
References 33 publications
3
152
0
Order By: Relevance
“…[1][2][3] A number of studies worldwide have reported favorable outcomes; 4-6 however, in some cases, ETV fails to resolve symptoms, even when it is technically successful with adequate patent stoma and fenestrated Lillequist membrane. [7][8][9][10][11] It has been hypothesized that patients might suffer from hydrocephalus caused by other obstructive membranes or by fibrosis in the subarachnoid space, especially around basal cisterns. Cine phase-contrast magnetic resonance imaging (PC MR) has been utilized as a method of distinguishing between ABSTRACT: Background: To predict success of endoscopic third ventriculostomy (ETV) in patients with obstructive hydrocephalus, we evaluated pre-and post-operative phase-contrast cine magnetic resonance images (PC MRI) on cerebrospinal fluid (CSF), cine flow in basal cisterns around the brain stem, and cervical medullar junction (CMJ) retrospectively.…”
mentioning
confidence: 99%
“…[1][2][3] A number of studies worldwide have reported favorable outcomes; 4-6 however, in some cases, ETV fails to resolve symptoms, even when it is technically successful with adequate patent stoma and fenestrated Lillequist membrane. [7][8][9][10][11] It has been hypothesized that patients might suffer from hydrocephalus caused by other obstructive membranes or by fibrosis in the subarachnoid space, especially around basal cisterns. Cine phase-contrast magnetic resonance imaging (PC MR) has been utilized as a method of distinguishing between ABSTRACT: Background: To predict success of endoscopic third ventriculostomy (ETV) in patients with obstructive hydrocephalus, we evaluated pre-and post-operative phase-contrast cine magnetic resonance images (PC MRI) on cerebrospinal fluid (CSF), cine flow in basal cisterns around the brain stem, and cervical medullar junction (CMJ) retrospectively.…”
mentioning
confidence: 99%
“…In these series cine MR imaging was only performed later than 1 year after ETV when there were symptoms of failure. Fukuhara and colleagues 7,8 used cine MR images to confirm an obstruction of the stoma, but only considered a cine MR imaging finding of obstruction diagnostic when the patients presented with signs of intracranial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…14,21,22,28,36,44) Subdural hygromas or effusions, which are not genuine subdural hematomas, may occur after shunting procedures or other neurosurgical interventions, but are usually absorbed postoperatively without evolution, unless infection or bleeding complications are present, and do not require surgical intervention. Hygromas usually have a benign course even as a post-shunt phenomenon, and will not need surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,14,16,17,25,30,40,43,46) Furthermore, injuries of vessels may cause various forms of minor or major hemorrhage (subarachnoid, intraventricular, and intracerebral). However, only three cases of subdural hematoma or hygroma after neuroendoscopic procedures have been reported.…”
Section: Introductionmentioning
confidence: 99%